2018
DOI: 10.1155/2018/4096845
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of MRI Abnormality Which Was Suspected as Sinusitis in Japanese Middle-Aged and Elderly Community Dwellers

Abstract: The aims of this study were to determine the prevalence of MRI abnormalities which were suspected as sinusitis in community-dwelling middle-aged and elderly Japanese and to identify risk factors for the MRI abnormality. Brain magnetic resonance imaging (MRI) data from the National Institute for Longevity Sciences, Longitudinal Study of Aging (NILS-LSA) were used for the analysis. Among the 2330 subjects in the NILS-LSA, 1933 participants were categorized as having no MRI abnormality or MRI abnormality using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…Compared to other studies that diagnosed paranasal sinusitis by means of MRI, the prevalence noted in our study was lower than that noted in studies from Denmark (31.7 %) 20 , Japan (33.8 %) 23 , and Norway (66 %) 12 . We believe that this variation could be due to the use of different diagnostic criteria and research techniques.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Compared to other studies that diagnosed paranasal sinusitis by means of MRI, the prevalence noted in our study was lower than that noted in studies from Denmark (31.7 %) 20 , Japan (33.8 %) 23 , and Norway (66 %) 12 . We believe that this variation could be due to the use of different diagnostic criteria and research techniques.…”
Section: Discussioncontrasting
confidence: 93%
“…Among all the participants in this study, 49.2 % were men. We found that men were approximately 86 % more likely to have paranasal sinusitis than women (adjusted OR = 1.86, 95 % CI = 1.54-2.24), which is consistent with the results of studies from Asia 21,23,27 . However, some surveys from developed Western countries found that women were at a higher risk of developing paranasal sinusitis 6,9,28 .…”
Section: Discussionsupporting
confidence: 90%
“…This wide range of variation in the reported prevalence rates can be attributed to heterogeneity in the study design, methodology, study population, and definitions of abnormal findings. 17 20 21 In our study population, 197 (32.0%) patients had abnormal findings in the paranasal sinuses. Mucosal thickening was the most common abnormal finding, followed by retention cysts.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, we considered patients who acquired a score ≥4 to have abnormal sinuses according to a study conducted in 2018. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we would hypothesize that any ancestry-based differences in sinusitis susceptibility linked to MS height dimensions are most likely to appear during late adolescence or early adulthood. Further, as there is some evidence that inferior pneumatization towards the maxillary alveolus may continue throughout adulthood-particularly due to tooth loss and alveolar resorption (Sperber, 2001; but see Ariji et al, 1994)-our results suggest that increased SFMS dimensions in older adults could be a contributing factor to their greater risk of developing sinusitis (Hoover et al, 1997;Slavin, 1997;Sugiura et al, 2018). For the purpose of this study, we avoided crania with moderate-to-severe alveolar resorption to mitigate the effects of the sinus floor (see Section 2); as such, both of these growthrelated possibilities warrant further investigation.As with previous studies investigating MS size and shape (Butaric & Maddux, 2016;Ikeda et al, 1998;Noback et al, 2016;S anchez Fern andez et al, 2000), our study further highlights the limited amount of clinically relevant information that can be gleaned from MS volume as an isolated measure of MS morphology.…”
Section: Discussionmentioning
confidence: 62%